Finite element analysis for CuO/water nanofluid in a partially adiabatic enclosure: Inclined Lorentz forces and porous medium resistance - Arif Ullah Khan; Naeem Ullah; Abdou Al-Zubaidi; Sohail Nadeem (Alexandria Engineering Journal, 2022)
Flow and heat transfer dynamics are considered quite complex phenomenon in different enclosures. Heat transport mechanism and its improvement due to the presence of nanoscale particles is vital topic of research. Owing to the widespread importance of free convection through fluids with nanoparticle in various configuration and constraint, we have addressed in this article the natural convection nanofluid flow in a hexagon shaped enclosure with heated cylinder. Simulation has been performed in the influence of porous medium and inclined magnetic field. The physical model is translated in terms of differential systems. For solutions purpose, the finite element method is utilized. The quantities of interest include the fluid flow and heat transfer aspects. The obtained results against flow controlling parameters are offered by means of contour plots and line graphs. It is noticed that the at lower Darcy number the heat transfer rates has diminishing behavior because of the higher porosity of medium. At higher Hartman number the velocity profile tends to decrease due to resistive nature of Lorentz forces. At maximum radius of heat source, the Nusselt number and velocity profile has higher values.